Koperasi : konsepsi, pemikiran, dan peluang membangun masa depan bangsa - Nasution, Muslimin, 1939- ([Jakarta] : Departemen Kehutanan dan Perkebunan RI, 1999)
Empowerment of cooperative societies and rural economy in the context of strengthening economic system of Indonesia.
Includes bibliographical references (p. 201-205).
Keywords: Cooperation -- Indonesia; Cooperative societies -- Indonesia